a(n)=12+(n-1)(3)

Simple and best practice solution for a(n)=12+(n-1)(3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a(n)=12+(n-1)(3) equation:


Simplifying
a(n) = 12 + (n + -1)(3)

Multiply a * n
an = 12 + (n + -1)(3)

Reorder the terms:
an = 12 + (-1 + n)(3)

Reorder the terms for easier multiplication:
an = 12 + 3(-1 + n)
an = 12 + (-1 * 3 + n * 3)
an = 12 + (-3 + 3n)

Combine like terms: 12 + -3 = 9
an = 9 + 3n

Solving
an = 9 + 3n

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by 'n'.
a = 9n-1 + 3

Simplifying
a = 9n-1 + 3

Reorder the terms:
a = 3 + 9n-1

See similar equations:

| -6h+4=-10h+6 | | log(6x+12)=1+log(x-6) | | -2-y=-8(2+y) | | X*4+200=x*14-20 | | 50-10(x-5)= | | 6=30-8x | | 4(6v-1)(v-4)=0 | | F(x)=4x^2+32x | | 2x=55 | | 6u=3u+45 | | y*(2)*(-3)=30 | | 10*3x= | | 6x(1/10) | | y=30-8x | | 4x+3(x-2)=20-2(8-x) | | (1.3x+2.4)+(-6.1x-3.2)= | | (8-3)*7=8-(3*7) | | y*(-3)+(-1)=30 | | -11x+y+4x-8y= | | P(2)= | | w^2+11=24 | | 8(26-3x)=5(5x-27) | | 8x=12.8 | | 29=-2w+17 | | 4(x^2)-3=0 | | 4c+20=1c+20 | | 20*logx=120 | | 5=0.08x | | 20*logariphm(x)=120 | | X^2x+3=0 | | (3z-8)(4-z)=0 | | 4(x-3)=-24-13 |

Equations solver categories